Molecular and enzymatic studies of cyclodextrin glucanotransferase gene from Bacillus sp. TS1-1 - Rahman, Kamalesh (2005)
The 16s rRNA gene sequence from Bacillus sp. TS1-1 exhibited the closest match with Bacillus sp. NER (99%) and was identified as Bacillus sp. A cyclodextrin glucanotransferase (CGTase) gene of Bacillus sp. TS1-1 was isolated and cloned into Escherichia coli. Beginning from the TTG codon, there was an open reading frame composed of 2163bp (721 amino acids). The NH2 terminal position encoded a 46-amino acids signal peptide and followed by the mature enzyme of 675 amino acids. The deduced amino acid sequence of the mature CGTase from Bacillus sp. TS1-1 exhibited 98.7% homology with 96% identity to the CGTase sequence from alkalophilic Bacillus sp. 1-1. The recombinant CGTase of Bacillus sp. TS1-1 expressed in E.coli was successfully purified to homogeneity using ammonium sulfate precipitation, followed by a-cyclodextrin-bound-epoxy-activated Sepharose 6B affinity chromatography. The specific activity of the CGTase increased by approximately 280 fold, from 36.69 U/mg of proteins to 10289.23 U/mg of proteins. The purified CGTase enzymes exhibited a single band with molecular weight of 75kDa on SDS-PAGE. Biochemical characterization of the enzyme shows an optimum temperature of 60°C and optimum pH of 6.0. The enzyme was stable between pH 7 to pH 9 and temperature up to 70°C. The Km and Vmax values calculated were 0.52 mg/ml and 54.35 mg of ß-cyclodextrin/ml/min respectively. Sago starch was found to be the best substrate for cyclodextrin (CD) production among other starch sources (corn, rice, soluble and tapioca starch). Only β- and γ-CD were detected during the production of CDs. The CGTase produced about 86% of ß-CD from the total CDs production, using sago starch as substrate after 24 hours of incubation at 60oC, without adding any selective agent. The total ß-CD produced under the conditions mentioned above was 3.65 g/l.